Prognostic impact of minimal residual disease analysis by flow cytometry in patients with acute myeloid leukemia before and after allogeneic hemopoietic stem cell transplantation. (29th April 2014) - Bastos‐Oreiro, Mariana; Perez‐Corral, Ana; Martínez‐Laperche, Carolina; Bento, Leyre; Pascual, Cristina; Kwon, Mi; Balsalobre, Pascual; Muñoz, Cristina; Buces, Elena; Serrano, David; Gayoso, Jorge; Buño, Ismael; et al.
Abstract Allogeneic stem cell transplantation (allo‐SCT) has become the treatment of choice in patients with intermediate‐risk and high‐risk acute myeloid leukemia (AML). The quality of response to treatment, assessed in terms of detection of minimal residual disease (MRD), has been consistently associated with prognosis and clinical outcome in patients with AML. The aim of the present study was to evaluate the prognostic impact of analyzing MRD in bone marrow using 4‐color multiparametric flow cytometry (MFC) in 29 patients with AML before and after allo‐SCT. Eighteen patients who were shown to be MRD‐negative [≤0.1% leukemia‐associated immunophenotypes (LAIPs)] by MFC at transplantation and underwent allo‐SCT had lower rates of relapse (15% vs. 66%, P = 0.045), better overall 1‐yr survival (83% vs. 52%, P = 0.021) and a lower cumulative incidence of relapse (P = 0.032) than patients who were MRD‐positive (>0.1%). All post‐transplant MRD‐positive patients underwent a therapeutic intervention after transplant (tapering of immunosuppression, donor lymphocyte infusion, or re‐transplant) with the intention of preventing relapse. Disease was controlled and MRD disappeared in five of these patients. Disease recurred in the other seven patients. We can conclude that follow‐up with MFC for the detection of MRD in AML before and after SCT is useful for predicting relapse. In the post‐transplant setting, monitoring of MRD by MFC could be a key preemptive intervention.